2015
DOI: 10.1002/elps.201400534
|View full text |Cite
|
Sign up to set email alerts
|

Capillary zone electrophoresis method for the direct determination of amino acids in recombinant human erythropoietin preparations used for the treatment of anemia

Abstract: A method based on CZE for the determination of glutamic acid, glycine, and alanine in a biopharmaceutical formulation containing recombinant human erythropoietin was developed. The separation was achieved within less than 5 min, using a fused-silica capillary column (55 cm × 50 μm id) and 30 mmol/L phosphate buffer at pH 11.5, containing 0.6 mmol/L CTAB and 10% v/v methanol, as BGE solution. Applied potential of -25 kV, temperature of 15°C and hydrodynamic injection time of 15 s, at 50 mbar, were employed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Glu, Gly and Ala are found in these formulations. CZE was used to analyse the AAs without any derivation with a UV‐DAD device . The phosphate BGE was also modified with methanol and CTAB.…”
Section: Biomedical Analysesmentioning
confidence: 99%
“…Glu, Gly and Ala are found in these formulations. CZE was used to analyse the AAs without any derivation with a UV‐DAD device . The phosphate BGE was also modified with methanol and CTAB.…”
Section: Biomedical Analysesmentioning
confidence: 99%
“…In general, AAs need to be derivatized when direct UV detection is adopted, except one previously report by Crespo et al [21]. We checked the UV absorption spectrum of BCAAs, which owned a certain UV absorbance below 200 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Contactless conductivity detector (CCD) is an optional method and the LOD range is from tens to sub μmol/L [15,19,20]. Few reports except Crespo et al have described the glutamic acid, glycine and alanine without derivatization were detected by the direct CE-UV detection (at 220 nm) [21]. In addition, many studies have showed that indirect UV absorbance detection is an important and alternative tool for the analysis of AAs in their native state [22], but has not been successfully applied in the separation of BCAAs.…”
Section: Introductionmentioning
confidence: 99%
“…AA are used as excipients in pharmaceutical formulations because they do not interfere with the enzymatic activity or the functional structure of proteins. CE was demonstrated as a good method for the simultaneous determination of Glu, Gly, and Ala, without addition of any other reagent or derivatization reaction, in a biopharmaceutical formulation containing recombinant human erythropoietin, considered as revolutionary treatment of anemia .…”
Section: Ce In Clinical Biochemistrymentioning
confidence: 99%
“…Close to EOF, micelles permeate into a sample zone sweeping and concentrate the analytes into a narrow zone between the Buffer 2 and the sample zone. as a good method for the simultaneous determination of Glu, Gly, and Ala, without addition of any other reagent or derivatization reaction, in a biopharmaceutical formulation containing recombinant human erythropoietin, considered as revolutionary treatment of anemia [83].…”
Section: Ce In Clinical Biochemistrymentioning
confidence: 99%